A Longitudinal Study on the Development of the Professional Identity of Future Physics Teachers - dos Reis Belíssimo, Jéssica [UNESP]; Nardi, Roberto [UNESP] (The University of Sydney Library, 2024)
This article derives from a master’s thesis that sought to understand some aspects of physics undergraduates’ conceptions of scientific knowledge, science teaching, and the process of knowledge construction for teaching. This study is longitudinal; data were collected from admission to course completion with the goal of understanding the impact of the pedagogical project and course structure. The Pecheutian Discourse Analysis provided theoretical and methodological support for the development of this research. The analysis of the interviews and questionnaires revealed that the course’s pedagogical project and curricular structure play an important role in the changes in the conceptions of future Physics teachers and the construction of their teaching identity.
Keywords: Longitudinal Study; Physics Teacher Training; Teachers Identity